Rapid emergence of effect of atorvastatin on cardiovascular outcomes in the Collaborative Atorvastatin Diabetes Study (CARDS). - Colhoun, H; Betteridge, D; Durrington, P; Hitman, G; Neil, H; Livingstone, S; Thomason, M; Fuller, J (2005)
AIMS/HYPOTHESIS: The aim of this study was to determine the pattern of the effect of the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor atorvastatin on cardiovascular events in patients with type 2 diabetes and no prior history of cardiovascular disease (CVD). MATERIALS AND METHODS: A post hoc analysis of data from the Collaborative Atorvastatin Diabetes Study (CARDS), a randomised, placebo-controlled trial of 2,838 patients with type 2 diabetes, was performed. Patients received atorvastatin (10 mg daily) or placebo and were evaluated for cardiovascular and other outcomes over a median follow-up period of 3.9 years. Cox proportional hazards modelling was carried out, and the hazard ratios calculated for various times after randomisation to treatment were investigated. RESULTS: A reduction in the primary endpoint of major CVD events was apparent and statistically significant as soon as 18 months after treatment initiation. The effect of atorvastatin on CHD events was apparent by 6 months, and at 1 year was similar to the 37% relative risk reduction observed at trial closure. CONCLUSIONS/INTERPRETATION: Atorvastatin alters the pathogenesis of CVD rapidly, such that the effect on cardiovascular events is apparent within months of initiation of therapy.